Bake : my best ever recipes for the classics - Hollywood, Paul (Bloomsbury Publishing, 2022)
"The only book you'll ever need to create perfectly delicious cakes, pastries, biscuits, breads, pizzas and desserts time and time again. Featuring more than 80 recipes! -- Back cover.